Arabic Poetry-Based Character Teaching: Pride In Blameworthy Morals In Abbasid Poetry - Khalid Fahad Al-Bahlal (Ijaz Arabi Journal of Arabic Learning, 2022)
Teaching Arabic poetry in addition to learning vocabulary and the uniqueness of Arabic literature students can also learn character. Such as the importance of preserving the moral values, and blameworthy morals, and emphasizing that the violators' existence promotes virtuous morals values, with opposition things are characterized. The nations' power is represented by morals power. The research problem is that blameworthy moral and moral revolt has never been investigated before. The poets expressed their viewpoints that are contrary to the general prevailing, the importance of promoting honored meanings, and staying away from its opposites. The descriptive method and analytical inductive of much Abbasid poetry were used. The result is to warn against revolting and to prove the opposition's existence. The values give humans a lofty goal to pursue, whether they are of his mind, or subject to his Lord's orders. The researcher highlights the morals and warns against their nastiness. By conducting studies on the morals origins and its branches with the witnesses call and proverbs of the Arabs' poetry from various times, the Arabs' poetry contains abundant material of pride in virtuous morals with an interest in clarifying the revolting of poets.